2021
DOI: 10.1111/jeb.13968
|View full text |Cite
|
Sign up to set email alerts
|

Mutation accumulation in inbreeding populations under evolution of the selfing rate

Abstract: Self-fertilization is common in hermaphroditic plants and also occurs in some co-sexual animals (Jarne & Charlesworth, 1993). Compared to outcrossing, self-fertilization enjoys an automatic transmission advantage, since a selfing individual not only transmits both its own male and female gametes to its offspring, but also can fertilize other individuals through pollen dispersal (Lande and Schemske, 1985;Lloyd, 1979;Nagylaki, 1976;). Selfing can also provide reproductive assurance when mates of mating opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…The model captures the coevolution between the selfing rate, inbreeding depression and genetic load, but does not account for the accumulation of deleterious mutations. Therefore, the model tends to slightly overestimate fitness, since mutation accumulation is likely to occur when the population size becomes small (Charlesworth et al 1993, Xu 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…The model captures the coevolution between the selfing rate, inbreeding depression and genetic load, but does not account for the accumulation of deleterious mutations. Therefore, the model tends to slightly overestimate fitness, since mutation accumulation is likely to occur when the population size becomes small (Charlesworth et al 1993, Xu 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…Selfing is often controlled by multiple modifier loci, and a recent study shows that the genetic architecture of selfing can affect the rate of mutation accumulation (Xu 2021). It is thus critical to know whether the evolution of selfing is more likely when the selfing rate is controlled by many slight-effect modifier loci or few large-effect loci.…”
Section: Effects Of the Genetic Architecture Underlying Selfingmentioning
confidence: 99%
“…Using simulations incorporating both selfing modifiers and deleterious mutations, Damgaard (1996) found weak frequency-dependent selection on a selfing modifier, which he explained as a result of variation of the number of deleterious mutations among individuals. A recent study showed that under coevolution, the genetic architecture of selfing and inbreeding depression can mutually affect the temporal dynamics of selfing rate and mutation accumulation (Xu 2021). Therefore, a multilocus model that incorporates both viability and modifier loci under a finite population size is needed to better predict the coevolution of selfing and inbreeding depression in small populations.…”
Section: Incorporating the Genetic Basis Of Inbreeding Depression N/amentioning
confidence: 99%
“…A modifier enhancing selfing can develop association with fitter alleles by promoting segregation and, thus, may invade even when ID is high ( Holsinger, 1988 ; Uyenoyama and Waller, 1991a , 1991c ). Conversely, in a highly selfing population, an outcrossing-enhancing modifier may invade under low ID ( Kamran-Disfani and Agrawal, 2014 ; Xu, 2022 ) because outcrossing promotes effective recombination between loci, thus increasing the efficacy of selection ( Uyenoyama and Waller, 1991a ). However, that genetic associations with fitness alleles may only slightly affect the invasibility of a selfing rate modifier, unless the modifier or deleterious mutations have strong effects ( Charlesworth et al., 1991 , 1992 ; Schultz and Willis, 1995 ; Damgaard, 1996 ).…”
Section: Introductionmentioning
confidence: 99%